(untitled) (Collection of scientific works «Scientific Problems of Architecture and Urban Planning» | ODABA, 2025)
We live in an era of increased mortality in our country, and thus the theme of death, both as a philosophical-metaphysical concept and as a daily reality, permeates the work of many cultural and artistic figures in Ukraine. Death has been understood in various ways, often signifying not merely the end of existence, but a transition to a new form of life. Funerary structures (architecture of death) serve as gateways or portals to another world. Many architects have posited that architecture begins at the burial site - “the space of lived experience.” Sacred spaces are unique in their ability to achieve such a profound phenomenological rooting in their environment. The forms and spaces of these sites transcend the mundane and the momentary in their search for eternal truths, perfection, and divinity. Churches, memorials, historical buildings (tombs), symbolic attributes, morgues, and spatial planning collectively shape the spiritual landscape of traditional funerary culture. Within the context of social interaction, there exists a triad of nature, architecture, and people. The “gaze of the era” and social landscapes reflect dominant views and values, showcasing cultural and national identities. Thus, the spiritual landscapes of sacred places, arising at the intersection of emotions and abstractions, can be characterized as emotional (sensitive) or tactile landscapes. Aggressive materialism has deliberately shattered all symbols and values of the previous era “to smithereens” in Odesa and its region. Alongside the significant loss of temples, sacred sites such as the First Christian Cemetery, the Jewish Cemetery, monastic cemeteries, and the Resurrection Skete have also been destroyed. The burial grounds of Odesa are an integral part of our lives and serve as evidence of what once transpired in our land; in fact, they function as open-air museums. In Ukraine, there is no law protecting spaces of memory, and many historical graves are in decay, 99% of which are not listed in the registers of monuments, despite being incredible works of art.